The Influence of transformational Leadership Style on Improving Employee Performance at PT. Plantation of The Nusantara XIV City of Makassar - Sarah Riani; Uhud Darmawan Natsir; Chalid Imran Musa; Muh. Ichwan Musa; Burhanuddin (PT Maju Malaqbi Makkarana, 2023)
The goals of this study at PT. plantation of the nusantara XIV city of makassar was to assess the effect of leadership styles on worker performance. The data used in this study were both primary and secondary, with a total sample of 42 employees. In this study, a quantitative technique was employed to evaluate the two hypotheses, and the data was processed using SPSS 2.5 and a simple linear regression analysis procedure. with a coefficient of determination of 0.297, the results demonstrated that the transformational leadership style variable limit a substantial influences on employees performance. Employee performance characteristics have a substantial influences of 0.50. According to the research's conclusions, both individually and together, independent factors have a substantial impacts on the performance of the dependent variables, PT. plantation of the nusantara XIV city of makassar. Therefore, the performance of the employee will certainly improve if the Transformational Leadership Style is further developed.